1999
DOI: 10.1086/520443
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Human Immunodeficiency Virus–Infected Patients to Antiretroviral Therapy

Abstract: The impact of demographic, psychosocial, and medical regimen-related variables on adherence of 123 human immunodeficiency virus (HIV)-infected patients to antiretroviral therapy was assessed by means of refill methodology. Satisfaction with social support (P = .029), problem-focused coping (P = .027), and active-behavioral coping (P = .011) correlated significantly with adherence, whereas loss of motivation (P = .006), hopelessness (P = .16), and avoidant coping (p = .015) correlated with nonadherence. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
165
2
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 20 publications
11
165
2
8
Order By: Relevance
“…The finding that avoidant coping is associated with intentional nonadherence is in line with previous literature (Halkitis, Parsons, Wolitski, & Remien, 2003;Singh et al, 1999;Weaver et al, 2005). Individuals who use avoidant coping strategies may choose to escape the stressors when dealing with the disease and therefore, be less likely to take an active role in their medication management.…”
Section: Factors Associated With Intentional Nonadherencesupporting
confidence: 91%
“…The finding that avoidant coping is associated with intentional nonadherence is in line with previous literature (Halkitis, Parsons, Wolitski, & Remien, 2003;Singh et al, 1999;Weaver et al, 2005). Individuals who use avoidant coping strategies may choose to escape the stressors when dealing with the disease and therefore, be less likely to take an active role in their medication management.…”
Section: Factors Associated With Intentional Nonadherencesupporting
confidence: 91%
“…Researchers verified that the non-Caucasian patients were significantly more non-compliant than Caucasian patients (16) . In another study, the authors showed that there was a relative risk of 1.7 regarding non-white ethnicity (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Breakthrough drug resistance, followed by rising viral loads and clinical failure is relatively common, even with high levels of adherence. 16 This entails ongoing clinical and laboratory monitoring and access to second-line regimens. Side-effects of drugs, especially in the early period of treatment, occur relatively frequently, some of which are sufficiently dangerous to require modifications to treatment.…”
Section: Service Delivery Challenge: Antiretroviral Therapy As Chronimentioning
confidence: 99%